2013
DOI: 10.1108/17465681311297667
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of care as a determinant for stakeholder inclusion and CSR perception in business education

Abstract: PurposeThe aim of the paper is to show that, among business students, care ethics is a determinant for CSR perception and stakeholder inclusion.Design/methodology/approachThe research was conducted utilising a quantitative approach. The population for this study consisted of students from a leading French business school.FindingsStakeholder inclusion is related to care ethics among students. CSR perception is related to stakeholder perception. CSR perception is related to care ethics.Research limitations/impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…This potential relationship between ethic of care and stakeholder theory is paramount for CSR issues, because stakeholder theory is said to be the dominant paradigm in CSR (McWilliams and Siegel, 2001). Research result by Andre (2013) which examines ethic of care as a determinant of stakeholder inclusion and CSR perception in business education that shows stakeholder inclusion is related to ethic of care. CSR perception is related to stakeholder perception.…”
Section: Student Ethicmentioning
confidence: 99%
“…This potential relationship between ethic of care and stakeholder theory is paramount for CSR issues, because stakeholder theory is said to be the dominant paradigm in CSR (McWilliams and Siegel, 2001). Research result by Andre (2013) which examines ethic of care as a determinant of stakeholder inclusion and CSR perception in business education that shows stakeholder inclusion is related to ethic of care. CSR perception is related to stakeholder perception.…”
Section: Student Ethicmentioning
confidence: 99%
“…This is supported by Barrena-Martinez et al [57] who concluded that social integration factors have a greater impact on the perception of CSR than explanatory factors. The CSR-sensitive mindset of students can be trained in cases in which the curriculum integrates care theory with CSR teaching [58].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While researchers from Western countries sometimes show the ongoing withdrawal of enterprises from the very idea of CSR and present themselves to stakeholders by imitating CSR as one of the marketing tools [3][4][5][6], or even lobbying [7] (pp. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], it is becoming a clear trend in post-Soviet countries. Therefore, attention is paid to the fact that the implementation of CSR should be oriented not towards charity, marketing, and public relations, but should first and foremost be understood as social responsibility towards stakeholders [8].…”
Section: Introductionmentioning
confidence: 99%
“…By adopting the practices and values of caring in CSR, organizations can significantly strengthen their impacts on the community. Caring is a universal human attribute, which is the foundation of morality ( André, 2013 ). Behind the donation behavior of corporations, we find concern for people in need under the theoretical framework of the ethics of care.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Initially, Gilligan (1982) proposed the ethics of care theory and was considered by some as a feminist perspective of ethics. However, the theory has been re-examined and defined “ as an empathic disposition which is translated into practices for the sake of other human beings ” ( André, 2013 : 35), evolving towards a care-based morality ( Formentin and Bortree, 2019 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%